The (im)possibilities of queer girlhoods: Chinese girls negotiating queerness and filial piety. Issue 2 (June 2023) - Xie, Xumeng
This paper examines the experiences of nine Chinese girls and young women as they explore and negotiate queer subjectivities within the constraints of patriarchal and (hetero)sexual norms surrounding girlhood and young femininity. I focus on filial piety ( xiaoshun ) as a normative gendered discourse being reconfigured in changing gender, familial and other power dynamics in China. I argue that the discourse of filial piety continues to naturalise a heteronormative girlhood that will smoothly transition into young womanhood prepared to take on responsibilities of 'getting married and having kids'. This narrative, however, is in tensions with girls and young women's diversified expressions of sexualities. Through the participants' own accounts of queer explorations, I demonstrate how they actively engage and reflect on these tensions with familial and filial discourses while navigating the (im)possibilities of becoming queer girls across varied socioeconomic and family backgrounds. The findings of this study offered new insights into how familism and filial piety are woven into Chinese gender and sexual politics and being constantly (re)negotiated. My conceptualisation of queer girlhoods in China shows how queer girls and young women are marginalised in and around family. In the meantime, it demonstrates the emergent strategies of queer resistance and negotiations of filial piety through delaying marriage and managing familial intimacy.